4x-6(3-x)=13

Simple and best practice solution for 4x-6(3-x)=13 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4x-6(3-x)=13 equation:


4x-6(3-x)=13

We simplify the equation to the form, which is simple to understand
4x-6(3-x)=13

Reorder the terms in parentheses
4x+(-18+6x)=13

Remove unnecessary parentheses
+4x-18+6x=+13

We move all terms containing x to the left and all other terms to the right.
+4x+6x=+13+18

We simplify left and right side of the equation.
+10x=+31

We divide both sides of the equation by 10 to get x.
x=3.1

See similar equations:

| 1.5x+.5=-1.0 | | 14*2=x | | 2-1=1 | | -5x-13=7 | | 2+4x=55 | | 3x+2=2(x+6) | | 2r-6(-10+r)=-7 | | 72-4x=5x+21 | | 7-2s+5s+8=13s+25-5s | | 5*2*(-4)+3*6= | | 20-x=-0.68*(20+x) | | x(x+8)-8(x+8)= | | 32-4=3x-26 | | 6x^2-60x+126= | | -3y+5y-4=-7+4y | | 6x^3+29x^2+27x-20=0 | | x^2+(k-1)x+4=0 | | -3h-1=11 | | 4x^2-x+11=0 | | 2x^4-4x^3+2x^2+2x= | | 2x^2-x+1=x^2-4x-1 | | 2+d=4d-2 | | 119-2x=25x+17 | | -3(x+4)=27 | | 6x-24=7 | | (x-2+i)(x-2-i)(x+3)=0 | | 5-8x=16-15x | | 7-2x=x-1 | | 9+6x-7-2x=55 | | 15-(-3)+4= | | 4(0,5x-3)-2(x+3)=3 | | 8x-36=4 |

Equations solver categories